2007
DOI: 10.1080/15376510601123195
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry and Integrated Virus Detection System Characterization of MS2 Bacteriophage

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. SPONSORING I MONITORING AGENCY NAME(S) AND ADDRESS(ES)10. SPONSORIMONITOR'S ACRONYM(S) SPONSORIMONITOR'S REPORT NUMBER(S) DISTRIBUTION I AVAILABILITY STATEMENTApproved for public release; distribution is unlimited. SUPPLEMENTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Using ES-DMA size distributions Pease et al (2011) determined the symmetry and number of proteins per capsid for PR772 (Family Tectiviridae, Genus Tectivirus), a biosafety level 1 (BSL1) simulant of adenovirus. Lute et al (2008) and Wick et al (2007) extended ES-DMA analyses to viruses of particular interest to biomanufacturers and filter firms by characterizing the size distributions of murine minute virus (Family Parvoviridae, parvovirus) and the BSL1 models, PP7 (Family Leviviridae, Genus Levivirus) and X174 (Family Microvaridae, Genus Microvirus) (Wick et al, 2007) used in virus filtration studies (Lute et al, 2008) and in the Parenteral Drug Association's (PDA) new nomenclature standards for small and large virus retentive filters. Wick et al (2005) demonstrated that ES-DMA is sufficiently gentle to enveloped viruses such as alphavirus (Family Togaviridae) although there was some loss of structure in murine hepatitis virus (Family Coronaviridae, Genus Coronavirus), and sendai rodent virus (Family Paramyxoviridae, Genus Respirovirus).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using ES-DMA size distributions Pease et al (2011) determined the symmetry and number of proteins per capsid for PR772 (Family Tectiviridae, Genus Tectivirus), a biosafety level 1 (BSL1) simulant of adenovirus. Lute et al (2008) and Wick et al (2007) extended ES-DMA analyses to viruses of particular interest to biomanufacturers and filter firms by characterizing the size distributions of murine minute virus (Family Parvoviridae, parvovirus) and the BSL1 models, PP7 (Family Leviviridae, Genus Levivirus) and X174 (Family Microvaridae, Genus Microvirus) (Wick et al, 2007) used in virus filtration studies (Lute et al, 2008) and in the Parenteral Drug Association's (PDA) new nomenclature standards for small and large virus retentive filters. Wick et al (2005) demonstrated that ES-DMA is sufficiently gentle to enveloped viruses such as alphavirus (Family Togaviridae) although there was some loss of structure in murine hepatitis virus (Family Coronaviridae, Genus Coronavirus), and sendai rodent virus (Family Paramyxoviridae, Genus Respirovirus).…”
Section: Introductionmentioning
confidence: 97%
“…Over the last decade, ES-DMA has been applied broadly to characterize phage and virus-like particles. For example, a number of studies measured the size of both large and small viruses (Bacher et al, 2001;Bothner and Siuzdak, 2004;Wick et al, 2005;Hogan et al, 2006;Thomas et al, 2004;Cole et al, 2009;Kaddis et al, 2007;Laschober et al, 2008;Pease et al, 2009;Wick et al, 2007). Using ES-DMA size distributions Pease et al (2011) determined the symmetry and number of proteins per capsid for PR772 (Family Tectiviridae, Genus Tectivirus), a biosafety level 1 (BSL1) simulant of adenovirus.…”
Section: Introductionmentioning
confidence: 99%
“…After centrifugation, ultrafiltration and acidification, the diluted solution of MS2 protein extract yielded coat protein signals after direct injection to ESI-MS. The identity of the proteins was verified by ESI-MS/MS (Top-down) by Cargile et al [ 51 ] and Wick et al [ 52 ]. An even more sophisticated approach is represented by LC-ESI-MS/MS of phage proteins digested by trypsin [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wick et al 33 reported that MS2 could survive in 0.1 mol/L HNO 3 for 66 h without losing phage particles. Höglund et al 34 studied bacterial viruses in source-separated urine, concluding that these viruses could be found there (pH 9).…”
Section: Influence Of External Factors On Phagesmentioning
confidence: 99%